Indonesian Mom-Influencers: The New Representative Faces of Corporations through Instagram Studying the Effect of Endorsers and Corporate Credibility on Consumer Attitude and Purchase Intention - Aditya, Febiyana; Rachma, Nabila; Kosasih, Dicky Mikhael; Gunadi, Willy (SBM ITB, 2021)
Abstract. Mom-influencers are a new medium used by businesses to reach a market segment of young mothers. This phenomenon has developed as young mothers increasingly turn to social media for up-to-date information on how to parent and what products they need. This study explores the effect of the credibility of mom-influencers as endorsers and corporate credibility on consumers' attitudes towards advertisements, attitudes towards the brand, and purchase intention. This study targeted Indonesian participants who followed an Instagram-verified mom-influencer page on their Instagram account. The data were collected with an online questionnaire and processed using partial least squares structural equation modelling (PLS-SEM). The results show that corporate credibility determines Indonesian consumers' attitudes towards advertisements and brands, as well as purchase intention. Meanwhile, source credibility boosts corporate awareness by gaining consumer attention through promotions.Keywords: Attitude, Credibility, Mom-Influencers, Purchase IntentionAbstrak. Mom-influencer adalah media baru yang digunakan oleh bisnis untuk menjangkau segmen pasar ibu-ibu muda. Fenomena ini telah berkembang ketika ibu-ibu muda semakin banyak beralih ke media sosial untuk mendapatkan informasi terkini tentang cara menjadi orang tua dan produk apa yang mereka butuhkan. Studi ini mengeksplorasi efek kredibilitas mom-influencer sebagai endorser dan kredibilitas perusahaan pada sikap konsumen terhadap iklan, sikap terhadap merek, dan niat beli. Penelitian ini menyasar peserta Indonesia yang mengikuti akun mom-influencer yang terverifikasi Instagram di akun Instagram mereka. Pengumpulan data dilakukan melalui kuesioner online dan diproses menggunakan partial least squares structural equation modelling (PLS-SEM). Hasil yang didapat menunjukkan bahwa kredibilitas perusahaan menentukan sikap konsumen Indonesia terhadap iklan dan merek, serta niat pembelian. Sementara itu, kredibilitas dari sumber meningkatkan kesadaran perusahaan dengan mendapatkan perhatian konsumen melalui promosi.Kata kunci: Sikap, Kredibilitas, Mom-Influencers, Niat Beli